Coinhibitory receptor PD-1H preferentially suppresses CD4+ T cell–mediated immunity - Flies, Dallas B.; Han, Xue; Higuchi, Tomoe; Zheng, Linghua; Sun, Jingwei; Ye, Jessica Jane; Chen, Lieping (The Journal of Clinical Investigation, 2014)
T cell activation is regulated by the interactions of surface receptors with stimulatory and inhibitory ligands. Programmed death-1 homolog (PD-1H, also called VISTA) is a member of the CD28 family of proteins and has been shown to act as a coinhibitory ligand on APCs that suppress T cell responses. Here, we determined that PD-1H functions as a coinhibitory receptor for CD4+ T cells. CD4+ T cells in mice lacking PD-1H exhibited a dramatically increased response to antigen stimulation. Furthermore, delivery of a PD-1H–specific agonist mAb directly inhibited CD4+ T cell activation both in vitro and in vivo, validating a coinhibitory function of PD-1H. In a murine model of acute hepatitis, administration of a PD-1H agonist mAb suppressed CD4+ T cell–mediated acute inflammation. PD-1H–deficient animals were highly resistant to tumor induction in a murine brain glioma model, and depletion of CD4+ T cells, but not CD8+ T cells, promoted tumor formation. Together, our findings suggest that PD-1H has potential as a target of immune modulation in the treatment of human inflammation and malignancies.